Pengembangan Model Pembelajaran Project Based Learning Berbantuan Artificial Intelligence (AI) dalam Pembelajaran Menulis Karya Ilmiah Siswa Kelas XI - Mahmudah, Ita; Izzah, Izzah (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
This study aims to: (1) describe the needs of students in the Artificial Intelligence (AI)-assisted Project Based Learning learning model in learning to write scientific papers; (2) describe the needs of teachers in the Project Based Learning learning model assisted by Artificial Intelligence (AI) in learning to write scientific papers; (3) producing and designing a Project Based Learning learning model assisted by Artificial Intelligence (AI) in learning to write scientific papers; (4) describe the results of the validation of the Artificial Intelligence (AI)-assisted Project Based Learning learning model in learning to write scientific papers; (5) produce the results of the development of a Project Based Learning learning model assisted by Artificial Intelligence (AI) in learning to write scientific papers. This research method is research and development of modifications based on research needs, namely the combination of Borg and Gall with Dick and Carey. The data of this research is in the form of qualitative through interview techniques, and quantitative data through questionnaire techniques. The learning model was developed based on a questionnaire of the needs of grade XI students with an average of 83.95%, while the average teacher needs were 89.16%. The results of the learning model design include learning structure (syntax), reaction principles, social systems, support systems, as well as instructional and accompanying impacts. The validation test was carried out by experts consisting of material, language, and media experts. The results of the validation percentage, namely 94.07% material, 73.43% media, 87.5% language with an overall percentage of 85%. Based on the validation results, the Artificial Intelligence (AI)-assisted Project Based Learning learning learning to write scientific papers for students of grade XI MAN 1 Ogan Ilir was declared very feasible for use by students and teachers. Based on these results, the researcher recommends that other researchers continue testing this product, considering that the current research is still limited to the expert validation and revision stages.